Macrophage metabolism in atherosclerosis. Issue 19 (7th September 2017) - Bories, Gael F. P.; Leitinger, Norbert
Abstract : A key aspect of atherosclerosis is the maladaptive inflammatory response to lipoprotein accumulation in the artery. The failure to decrease lipid accumulation, to clear apoptotic cells, and to resolve inflammation ultimately leads to macrophage accumulation within the vascular wall [Thorp EB (2010) Apoptosis  15, 1124–1136; Moore K et al . (2013) Nat Rev Immunol 13, 709–721; Moore KJ and Tabas I (2011) Cell 145, 341–355; Ley K et al . (2011) Arterioscler Thromb Vasc Biol 31, 1506–1516]. Several subsets of macrophages are found inside atherosclerotic plaques [Chinetti‐Gbaguidi G et al . (2015) Nat Rev Cardiol 12, 10–17; Leitinger N and Schulman IG (2013) Arterioscler Thromb Vasc Biol 33, 1120–1126; Mantovani A et al . (2009) Arterioscler Thromb Vasc Biol 29, 1419–1423]: Proinflammatory M1‐like macrophages potentially participate in atherosclerosis initiation and progression; M2‐like macrophages are thought to be protective due to their anti‐inflammatory and profibrotic properties, presumably stabilizing the plaque [Chistiakov DA et al . (2015) Int J Cardiol 184, 436–445; Gordon S (2003) Nat Rev Immunol 3, 23–35]; Mox macrophages develop in response to oxidized phospholipids and present a glutathione‐ and potentially redox‐regulating phenotype [Kadl A et al . (2010) Circ Res 107, 737–746]; Mhem macrophages are found in areas of plaque hemorrhage [Boyle JJ et al . (2009) Am J Pathol 174, 1097–1108; Boyle JJ et al . (2012) Circ Res 110, 20–33] where they are involved in heme clearance. Recent evidence suggests that the relative abundance of these macrophage subsets is a better indicator of plaque progression and stability than the total number of lesion macrophages [Chinetti‐Gbaguidi G et al . (2015) Nat Rev Cardiol 12, 10–17]. Over the last few years, findings in the area of immunometabolism established a link between the metabolic state of the different macrophage phenotypes and their functions [O'Neill LAJ and Pearce EJ (2016) J Exp Med 213, 15–23]. However, the effect of metabolic changes in macrophages on atherosclerotic plaque progression and stability is not well understood and an area of intensive study. In this review, we will summarize and critically discuss recent developments in the field of macrophage metabolism in the context of atherosclerosis to guide future investigation in this area. Abstract :